2015
DOI: 10.13066/kspm.2015.10.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Forced Vital Capacity and Maximal Voluntary Ventilation Between Normal and Forward Head Posture

Abstract: | Abstract |1 ) PURPOSE:The purpose of this study was to investigate the vital capacity and maximal voluntary ventilationin subjects with forward head posture (FHP). METHODS:Twenty-eight subjects participated in this study (normal 14, FHP 14) and were resident in B city. The mean age, height and weight of subjects was 22.80yrs, capacity between normal and FHP subjects. All statistical analyses were performed using SPSS 21.0 for window versionand p-values less than 0.05 were used to identify significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…FHP is also known to affect respiratory function due to weakness and imbalance in the respiratory muscles [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FHP is also known to affect respiratory function due to weakness and imbalance in the respiratory muscles [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As the head moves forward, the inhalation muscles such as sternocleidomastoid, scalenus, suboccipitalis are shortened, limiting the expansion of the rib cage This restriction of rib mobility reduces the amount of air that enters the lungs [6,8,9]. Another study analyzed the relationship between the craniovertebral angle and respiratory circulatory function, and showed that the smaller the craniovertebral angle, the less carbon dioxide emission.…”
Section: Introductionmentioning
confidence: 99%
“…The value of FVC may depend on the movement of the diaphragm and the extent of thoracic cage expansion. 12 Also, in order to achieve this forced expiration, the volume in the thoracic cavity must be reduced rapidly, and transversus abdominis, external oblique abdominal, internal oblique abdominal and rectus abdominis muscle must be actively contracted. 23 For the women in their twenties, we can consider that contraction of transverse abdominis by the application of Figure-8 brace caused elevation of diaphragm to the thoracic cavity by the increase of abdominal pressure, and facilitated exhalation of breath.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Han et al measured FVC and maximal volume ventilation (MVV) in young adults, and found that FHP was less comparable to FVC, FEV1, and Ratio of FVC to FEV1, MVV showed lower results than normal posture. 12 Azadinia et al improved posture stability and balance by wearing the posture-training support and spinomed orthosis which is thoracolumbaosacral orthosis 13 Lee et al For those with a round shoulder posture, measurement was made by wearing a Figure-…”
Section: Introductionmentioning
confidence: 99%
“…Han et al 12 ) studied a normal posture group and a forward head posture group and found that FVC, FEV1, and maximum voluntary ventilation (MVV) were all decreased in the forward head posture group. According to Lee and Chu 13 ) , there were positive correlations between the CVA and oxygen uptake and CO 2 emission, which indicates that respiratory activity decreases as the angle of the forward head posture is reduced.…”
Section: Discussionmentioning
confidence: 99%